2021
DOI: 10.1088/1742-6596/2142/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet transform-based cross-correlation in the time-delay estimation applications

Abstract: The article discusses the application of wavelet analysis for the time-frequency time-delay estimation. The proposed algorithm is wavelet transform-based cross-correlation time delay estimation that applies discrete time wavelet transform to filter the input signal prior to computation of cross-correlation function. The distinguishing feature of the algorithm that it uses the variation of continuous wavelet transform to process the discrete signals instead of dyadic wavelet transform that is normally applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…In this paper, we studied the practical applicability of the WCC algorithm proposed and described in [19]. The study confirmed that the WCC method can make a useful tool in the leak noise correlator software.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In this paper, we studied the practical applicability of the WCC algorithm proposed and described in [19]. The study confirmed that the WCC method can make a useful tool in the leak noise correlator software.…”
Section: Discussionsupporting
confidence: 53%
“…For signal processing, the mathematical apparatus of continuous wavelet transform (CWT) was applied. The implementation of CWT to correlation analysis of time series is described in more detail in [19]. The signal processing algorithm is briefly introduced and explained in the final part of this section.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations